HISTOLOGICAL CHANGES OF STRUCTURAL COMPONENTS IN LYMPH NODES OF RATS AND CHANGES IN BIOCHEMICAL BLOOD INDICES IN EXPERIMENTAL OBESITY - Harapko, T.V. (World of Medicine and Biology, 2020)
The article analyses the results and data of experimental study performed on white female and male rats of reproductive age (2.5-3.5-months). The purpose of the study was to establish the histological changes of rat lymph nodes structural components and changes in biochemical blood parameters through different terms of experimental obesity. The biochemical analysis of white male and female rats’ blood for the level of glucose, ALT, AST, cholesterol and triglycerides was carried out throughout the experiment. After one week of experiment, there is an insignificant expansion of the marginal and cortical lymphatic sinuses. With the experiment duration increase all pathological changes exacerbate.
Keywords: obesity; experiment; rat; lymph node; lymphocytes